risk factor of stunting based on WHO conceptual framework on Childhood Stunting - Aulia, Fivi; Oktriani, Tuti (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: The stunting rate in Indonesia in 2022 was 21.6%. I was reduced when compared to the SSGI data in 2021 of 24.4%. Stunting prevention is a much more effective step than stunting treatment itself. Prevention of stunting can be done by optimizing the role of mothers in the golden phase of child development. Stunting can be prevented by implementing infant and child feeding, which consists of Early Initiation of Breastfeeding (IMD), exclusive breastfeeding, and timely initiation of complementary feeding. Unfortunately, the achievement of this component of infant and child feeding practices is still far from the target. In 2022, the percentage of infants who received exclusive breastfeeding was 69.7%. Objective of this study is to analyze the risk factors for stunting based on the WHO Conceptual Framework on Childhood Stunting.. Methods: It was an analytic observational study using a case–control design, which examines the relationship between research factors or exposures and disease by comparing a case group (stunted children under five years of age) with a control group (children under five years of age with normal growth). Results: The results of the Chi-square test indicate a statistically significant association between exclusive breastfeeding and the occurrence of stunting in children (p-value = 0.04), no statistically significant association between breastfeeding for two years and the occurrence of stunting in children (p-value = 0.36), ignificant association between the timely provision of complementary feeding (MP-ASI) and the occurrence of stunting in children (p-value = 0.001). no statistically significant association between the appropriateness of infectious deasese history and the occurrence of stunting in children (p-value = 0.93). Conclusion: This study found that Exclusive breastfeeding and timely complementary feeding were significantly associated with stunting, while breastfeeding for two years and infectious disease history showed no significant association.